The influence of transformational leadership, organizational culture, and achievement motivation on teacher performance at SMKN 7 Surabaya through organizational commitment as a mediating variable - Kurniawan, Rizal; Andjarwati, Tri; Ardiana, Dewa Ketut Raka (Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to analyze the influence of transformational leadership, organizational culture and achievement motivation on teacher performance, mediate by organizational commitment. The samples in this research through a saturated sampling technique then get 100 teachers who worked at SMKN 7 Surabaya. Hypothesis testing in this research was carried out using a SMART-PLS. The results of this research say that transformational leadership (X1) and Achievement motivation (X3) influence organizational commitment (Z), while Organizational culture (X2) partially not influence organizational commitment (Z). Then transformational leadership (X1) and Achievement motivation (X3) not influence teacher performance (Y), while Organizational culture (X2) and organizational commitment (Z) influence teacher performance (Y). Additionally, regarding the indirect effects analysis, it was found that transformational leadership (X1) and achievement motivation (X3) influence teacher performance (Y) through the mediation of organizational commitment (Z). However, organizational culture (X2) not influence teacher performance (Y) through the mediation of organizational commitment (Z). Keywords: leadership, culture, motivation, commitment, performance